Seawater carbonate chemistry and growth and photosynthesis of a Great Barrier Reef Coralline Alga - Bonnie Lewis; Dorothea Bender-Champ; Sophie Dove; Guillermo Diaz-Pulido (PANGAEA, 2025)
This study examined the individual and interactive impacts of global and local stressors by investigating the effects of increased seawater pCO2, elevated nutrient concentrations and reduced light levels on linear growth and metabolic rates of the common branching crustose coralline alga Lithophyllum cf. pygmaeum. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from Figshare (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-02-24.